The intra-Andean borders: advances and setbacks - Ramírez, Socorro (2016)
This article analyzes the process of border integration within the Andean Community, starting from its beginnings and pointing out its strengths and weaknesses. The author examines the importance of the topic for Colombia, due to the fact that Colombia shares more borders than any other Andean country and because its internal conflict affects its neighbors. The article also suggests how the Andean Community should handle border issues in the short, medium, and long terms.